2013
DOI: 10.3168/jds.2012-5890
|View full text |Cite
|
Sign up to set email alerts
|

Experimental treatment of Staphylococcus aureus bovine intramammary infection using a guanine riboswitch ligand analog

Abstract: Staphylococcus aureus is a leading cause of intramammary infections (IMI). We recently demonstrated that Staph. aureus strains express the gene guaA during bovine IMI. This gene codes for a guanosine monophosphate synthetase and its expression is regulated by a guanine riboswitch. The guanine analog 2,5,6-triaminopyrimidine-4-one (PC1) is a ligand of the guanine riboswitch. Interactions between PC1 and its target result in inhibition of guanosine monophosphate synthesis and subsequent death of the bacterium. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…Based on the crystal structure of hypoxanthine bound to a guanine riboswitch (22), it was proposed that purine and pyrimidine analogs could also form a network of hydrogen bonds for proper complex formation between ligand and aptamer (7). A pyrimidine analog 2,5,6-triaminopyrimidin-4-one (PC1) was reported to kill S. aureus but not bacteria that lack guanine riboswitch control of guaA (7,8). We tested the antibiotic potential of PC1 against S. aureus, Staphylococcus epidermidis, Bacillus subtilis, Klebsiella pneumoniae, Enterococcus faecalis, and Escherichia coli and confirmed that PC1 indeed kills Staphylococcus but not the other Gram-positive and -negative bacteria examined (see Fig.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the crystal structure of hypoxanthine bound to a guanine riboswitch (22), it was proposed that purine and pyrimidine analogs could also form a network of hydrogen bonds for proper complex formation between ligand and aptamer (7). A pyrimidine analog 2,5,6-triaminopyrimidin-4-one (PC1) was reported to kill S. aureus but not bacteria that lack guanine riboswitch control of guaA (7,8). We tested the antibiotic potential of PC1 against S. aureus, Staphylococcus epidermidis, Bacillus subtilis, Klebsiella pneumoniae, Enterococcus faecalis, and Escherichia coli and confirmed that PC1 indeed kills Staphylococcus but not the other Gram-positive and -negative bacteria examined (see Fig.…”
Section: Figmentioning
confidence: 99%
“…The identity and purity of PC1 were verified in-house by liquid chromatography (LC) and mass spectrometry (MS). PC1 stock solutions (2 mg/ml) required 0.03 N NaOH and 1.5 mM dithiothreitol (DTT) to promote solubility and prevent oxidative self-condensation (7,8). All other compounds were made as 100 mM stocks in 0.1 N NaOH.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, they contain a pocket that can be targeted for developing new antibiotics. Indeed, it was shown that compounds binding to the guanine riboswitch in vitro have activity in an in vivo infection model [9][10][11]. Further, it was demonstrated that the antibiotic compounds pyrithiamine and roseoflavin most likely act via the thiamine pyrophosphate (TPP) and flavin mononucleotide (FMN) riboswitches, resp.…”
Section: Introductionmentioning
confidence: 99%
“…Three of these riboswitch classes have been revealed as important cellular targets of antibacterial small molecules whose mechanism of action had not been previously defined (9)(10)(11)(12)(13). More recently, several publications have demonstrated that novel small molecules that bind to selected riboswitch aptamers with affinities comparable to that of the cognate ligand can be rationally identified and optimized (14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%